QUALITY OF CORD STEEL 80 AFTER RECONSTRUCTION OF MNLZ-3 IN CONDITIONS OF RUP «BMZ» - N. A. Glazunova; T. I. Sidorenko; N. A. Hodosovskaja (Литьë и металлургия, 2011)
The theme of improvement of quality of the steel 80 intended for metal cord production, after reconstruction of machine of slugs continuous casting in the conditions of RUP «BMZ» is elucidated.